The Significance of Multidisciplinary Approach in Hadith Studies: A Case Analysis of Ma'had Aly Hasyim Asy'ari Tebuireng - Yahya, Yuniar Indra (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
In contemporary Islamic scholarship, the study of hadith is of paramount importance. However, Ma'had Aly Hasyim Asy'ari Tebuireng's multidisciplinary approach in hadith studies has not yet reached a third of the monodisciplinary research. This study addresses two main topics: first, the urgency of a multidisciplinary approach in hadith studies at Ma'had Aly; second, to describe the multidisciplinary approaches in hadith studies. The current state of hadith studies at Ma'had Aly Hasyim Asy'ari Tebuireng is predominantly monodisciplinary, with monodisciplinary research accounting for 70% of the theses from 2020 to 2023. In contrast, the multidisciplinary approach in hadith studies at Ma'had Aly Tebuireng remains below 10%. Therefore, it is essential to enhance the approaches that support hadith's research at Ma'had Aly Tebuireng, specifically by incorporating hermeneutics, stylistics, and ethno/netnography. These interdisciplinary methodologies offer a more nuanced and comprehensive analysis of hadith by integrating perspectives from various academic disciplines. This approach deepens the understanding of hadith and broadens the scope of research, making it more relevant to contemporary issues and diverse contexts.